(untitled) (Fiep Bulletin - online, 2015)
The leadership and stress are important factors to coaches in the process of training and performance of their teams. This Study has the objective to analyze the relation between leadership and stress in 47 athletes of volleyball of base categories of Paraná Clube, with age (x= 14,7 and s.d.= 1,59). It was used a Pearson correlation to leadership and stress with a significant level of p<0,05, data were treated with a statistic program for windows. In the correlation of stress and leadership, there was no significance between the variables. In this study with these subjects, there were no significant correlation between leadership and stress. The leaders presented a low stress level than the no leaders and all the athletes were in a high level of stress.